Respuesta :
To solve this we will use inverse operations.
The inverse operations for subtraction is addition.
y - 10 = 32
32 + 10 = 42
So, y = 42 BUT lets check our work.
42 - 10 = 32.
So y = 42.
The inverse operations for subtraction is addition.
y - 10 = 32
32 + 10 = 42
So, y = 42 BUT lets check our work.
42 - 10 = 32.
So y = 42.
y - 10 = 32
First, we have to make the variable (y) equal something. To do that, we have to do everything on one side of the problem. We can first start off by adding 10 to each side. This will make the variable equal the unknown answer.
[tex]y = 32 + 10[/tex]
Second, we can now add 32 + 10. Once adding that, you will have the answer to the unknown variable. 32 + 10 = 42.
[tex]y = 42[/tex]
Answer: [tex]\fbox {y = 42}[/tex]
First, we have to make the variable (y) equal something. To do that, we have to do everything on one side of the problem. We can first start off by adding 10 to each side. This will make the variable equal the unknown answer.
[tex]y = 32 + 10[/tex]
Second, we can now add 32 + 10. Once adding that, you will have the answer to the unknown variable. 32 + 10 = 42.
[tex]y = 42[/tex]
Answer: [tex]\fbox {y = 42}[/tex]